A dermatomyositis and scleroderma overlap syndrome with a remarkable high titer of anti-exosome antibodies - E. Avalos-Díaz; A. López-Luna; M.G. Pacheco-Tovar; V. González-Díaz; R. Gutiérrez-Ramos; R. Herrera-Esparza (PAGEPress Publications, 2011)
In 1972, Sharp et al described the mixed connective tissue disease; such a description corresponded to an apparently distinct rheumatic disease syndrome associated to U1RNP, which is an extractable nuclear antigen or ENA (1). After this clever description, different overlap syndromes that did not meet the EMTC criteria were described. Conceptually Alarcón-Segovia coined the term of "shared autoimmunity", which was defined by the presence of two or more data compatible with autoimmune disease; such category of disease describes signs or symptoms of certain autoimmune connective diseases, for instance Rupus corresponds to lupus erythematosus associated...